Education, employment, and land holding pattern in a Tamil village - Nair, K. N. (Working paper (Centre for Development Studies (Trivandrum, India)) ;, 1982)
Comparative study of Kadalhuchery Village in Kanyakumari District, Tamil Nadu, in 1961 and 1980.